2010
DOI: 10.1002/marc.201000021
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry on Electrospun Polymeric Nanofibers: Merely Routine Chemistry or a Real Challenge?

Abstract: Nanofiber-based non-wovens can be prepared by electrospinning. The chemical modification of such nanofibers or chemistry using nanofibers opens a multitude of application areas and challenges. A wealth of chemistry has been elaborated in recent years on and with electrospun nanofibers. Known methods as well as new methods have been applied to modify the electrospun nanofibers and thereby generate new materials and new functionalities. This Review summarizes and sorts the chemistry that has been reported in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 62 publications
0
70
0
Order By: Relevance
“…Like with Quat-12-PU-coated surfaces tested in this study, these nanofibers were found to exhibit excellent antibacterial activities against both E. coli and S. aureus (Table 6): the log-reductions were close to 7.5 for both cells. With polymeric nanofibers having potential to be used in fabrics, filters, and medical devices [23,24], those made from Quat-12-PU would have an added benefit of being antimicrobial.…”
Section: Determination Of Coating Cycle By Charge Density Of Quaternamentioning
confidence: 99%
“…Like with Quat-12-PU-coated surfaces tested in this study, these nanofibers were found to exhibit excellent antibacterial activities against both E. coli and S. aureus (Table 6): the log-reductions were close to 7.5 for both cells. With polymeric nanofibers having potential to be used in fabrics, filters, and medical devices [23,24], those made from Quat-12-PU would have an added benefit of being antimicrobial.…”
Section: Determination Of Coating Cycle By Charge Density Of Quaternamentioning
confidence: 99%
“…[8][9][10] Electrospun nanomaterials exhibit several amazing characteristics, such as remarkable specific surface area, flexibility in surface functionalities and superior mechanical performance. [11][12][13] Recently, many investigators have applied various measures to control this process in order to produce PU fibrous membranes with designed functions. [14][15][16] Demir et al [15] investigated the electrospinning process of PU fibers and demonstrated that the temperature, conductivity and viscosity of solution were the dominant factors controlling the fiber morphology.…”
Section: Introductionmentioning
confidence: 99%
“…A high surface area-to-volume ratio (which leads to high sorption capacity), porosity, and mechanical integrity are the benefits of electrospun fibers. The fibers also serve as substrates for functional groups upon surface modification [26,27]. They can thus be potentially used for sorption and desorption of metal ions.…”
Section: Introductionmentioning
confidence: 99%